Estilo gráfico: Análisis del rediseño de los símbolos de la Provincia de Los Ríos - Sevilla Cadena, Kerly Alejandra (2020)
In the present case study, the graphic style of the redesign of the symbols of the mayor of Babahoyo and that of the prefecture of Los Ríos was analyzed, since it was necessary to use a qualitative design through exploratory, diagnostic research and descriptive focused on interviewing and observation techniques, in order to detect the visual message that you want to project. The results of this research showed that, within the redesigns, the message to be transmitted is the renewal and differentiation of this new administration. Likewise, this study demonstrated the importance of visual communication, because this is a strategic tool that contains messages.